Kegiatan Kepedulian Sosial Melalui Penyaluran Sembako dan Makanan Gratis bagi Masyarakat Kurang Mampu di Wilayah Tropodo - Mujito Mujito; Juliana Hikmatul Izmy; Rahayu Mardikaningsih; Didit Darmawan; Aisatul Mufarrohah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
A Community Service (PkM) activity through the distribution of free basic food packages was carried out in the Tropodo area. This activity was carried out because there are still people who are unable to meet basic living needs, especially those related to food needs. Therefore, students and lecturers of Sunan Giri University Surabaya carried out community service activities to help their food needs while demonstrating a tangible form of concern for others. This activity used the Participatory Learning and Action (PLA) method, an approach model that focuses on community empowerment and emphasizes strategies for distributing free basic food packages so that they can be distributed to the right people. Direct aid distribution activities can create a space for sincere interaction with the community as a form of social care. This aims to instill an attitude of mutual care and can minimize individualism in society. The results of this community service activity show that social care manifested through real actions can help people in need and can increase empathy within oneself.